Effect of traditional Asian exercise on patients with chronic heart failure: a protocol for network meta-analysis of randomised controlled trials - Yan Li; Qian Lin; Zhuo Zhang; Lintong Yu; Kun Zhou; Jie Wan; Xiang Ji; Jianglin Xu; Ruli Feng; Jialin Jin; Cong Huang; Tianshi Mao (BMJ Open)
Introduction Chronic heart failure (CHF) is a common disease worldwide, and imposes a substantial burden to the healthcare system. In CHF, limited exercise capacity and affected mental well-being leads to a reduced quality of life (QOL). How to improve the QOL and exercise endurance is critical for patients with CHF. Exercise therapy, such as some traditional Asian exercises (TAEs) including Taichi, Baduanjin and Yoga, plays an important role in the rehabilitation of patients with CHF. TAE is suitable for the rehabilitation of patients with CHF because of its soft movements and can relax the body and mind. Studies have shown that TAE can regulate the overall health status of the body and exercise tolerance, improve QOL and reduce rehospitalisation rate in patients with CHF. However, the difference in efficacy of TAE in patients with CHF is not yet clear. The main purpose of this study is to conduct a network meta-analysis (NMA) of randomised trials to determine the impact of TAE on patients with CHF of different types, different causes and different New York Heart Association (NYHA) heart function classifications and to provide references for different types of patients with CHF to choose appropriate exercise rehabilitation therapy.Methods and analysis The literature search will be retrieved from PubMed, the Cochrane Library, Embase, Web of Science, Chinese National Knowledge Infrastructure, Wanfang database, Chinese biomedical literature service system (SinoMed) and Chinese Scientific Journals Database (VIP) from the date of their inception until 1 August 2021. All randomised controlled trials that evaluated the effects of three different TAE therapies (Taichi, Baduanjin and Yoga) on patients with CHF will be included. The primary outcomes are peak oxygen uptake (peak VO2), exercise capacity (6-min walking distance) and QOL tested with the Minnesota Living with Heart Failure Questionnaire. Secondary outcomes include the levels of N-terminal pro brain natriuretic peptide, left ventricular ejection fraction, systolic blood pressure and diastolic blood pressure. For included articles, two reviewers will independently extract the data, and Cochrane Collaboration’s tool will be used to assess risk of bias. We will perform the Bayesian NMA to pool all treatment effects. The ranking probabilities for the optimal intervention of various treatments (Taichi, Baduanjin or Yoga) will be estimated by the mean ranks and surface under the cumulative ranking curve. Subgroup analysis for different types, different causes and different NYHA heart function classifications of CHF will be performed. We will use the Grading of Recommendations Assessment, Development and Evaluation system to assess the quality of evidence contributing to each network estimate.Ethics and dissemination The results will be disseminated through peer-reviewed publications. They will provide useful information to inform clinicians on the potential functions of TAE in CHF, and to provide consolidated evidence for clinical practice and further research of TAE.PROSPERO registration number CRD42020179304.